Kompetensi Sumber Daya Manusia Dalam Meningkatkan Kualitas Informasi Keuangan UMKM - R Ait Novatiani; Veronica Christina; Robertus Ary Novianto; Tetty Lasniroha Sarumpaet; Aida Wijaya (Politeknik Ganesha Medan, 2025)
UMKM actors experience difficulties in presenting financial information based on SAK-EMKM, the reason is that MSME actors do not have the ability to present quality financial information. Therefore, in order for UMKM financial information to have quality, it can be realised with competent human resources. This research aims to analyse human resources that have competence, UMKM financial information that has quality and test human resource competencies that affect quality financial information. The population is UMKMs in the agricultural sector in Mekarmanik Village, Cimenyan District, Bandung Regency, totalling 50 people. The findings show that human resource competencies are good, UMKM financial information is of high quality and human resource competencies have an influence on the quality of UMKM financial information.